Cervical Spondylotic Myelopathy Secondary to Dropped Head Syndrome: Report of a Case and Review of the Literature - Abolfazl Rahimizadeh; Housain F. Soufiani; Saghayegh Rahimizadeh (Case Reports in Orthopedics)
The dropped head syndrome (DHS) is a disabling condition caused by severe weakness of the neck extensor muscles causing progressive reducible kyphosis of the cervical spine and the inability to hold the head up. Weakness can occur in isolation or in association with a generalized neuromuscular disorder. Isolated cases are owed to the late onset of noninflammatory myopathy designated as INEM, where persistent chin to chest deformity may gradually cause or aggravate preexisting degenerative changes of the cervical spine and ultimately result in myelopathy. In review of the literature, we could find only 5 cases, with no unique guidelines to address the management of these two concomitant pathologies. Herein, a 69-year-old man who had developed cervical myelopathy 2 years after being affected by isolated dropped head syndrome is presented. Chin to chest deformity and cervical myelopathy were managed through three-level anterior cervical discectomy and fusion (ACDF) combined with decompressive cervical laminectomy and stabilization with C2 to C7 pedicle screw-rod construct. At 4-month follow-up, despite recovery in patient’s neurological status, flexion deformity reappeared with recurrence of dropped head due to C7 pedicle screws pull-out. However, this was successfully managed with extension of the construct to the upper thoracic levels.